Effects of Climate on Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) Growth Southeast of the European Alps - Tom Levanič; Hana Štraus (Plants, 2022)
Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) is a non-native tree species in Slovenia with the potential to partially replace Norway spruce in our native forests. Compared to spruce, it has several advantages in terms of volume growth, wood quality and tolerance to drought. This is important given the changing climate in which spruce is confronted with serious problems caused by increasing temperatures and drought stress. At three sites (one on non-carbonate bedrock and deep soils, and two on limestone with soil layers of varying depths), 20 Douglas-fir and 20 spruce per site were sampled in order to compare their radial growth response to climate and drought events. The radial growth of Douglas-fir exceeds that of spruce by about 20% on comparable sites. It is more responsive to climate than spruce. Above-average temperatures in February and March have a significant positive effect on the radial growth of Douglas-fir. In recent decades, above-average summer precipitation has also had a positive influence on the radial growth of Douglas-fir. Compared to spruce, Douglas-fir is less sensitive to extreme drought events. Our results indicate that Douglas-fir may be a good substitute for spruce in semi-natural managed forest stands in Slovenia. The planting of Douglas-fir should be allowed in Slovenian forests, but the proportion of it in forest stands should be kept lower than is the case with spruce today.